Responsive Fluorophore Aggregation Provides Spectral Contrast for Fluorescence Lifetime Imaging. (16th April 2020) - Schleyer, Kelton A.; Datko, Benjamin D.; Burnside, Brandon; Cui, Chao; Ma, Xiaowei; Grey, John K.; Cui, Lina
Abstract: Fluorophores experience altered emission lifetimes when incorporated into and liberated from macromolecules or molecular aggregates; this trend suggests the potential for a fluorescent, responsive probe capable of undergoing self‐assembly and aggregation and consequently altering the lifetime of its fluorescent moiety to provide contrast between the active and inactive probes. We developed a cyanobenzothioazole‐fluorescein conjugate (1 ), and spectroscopically examined the lifetime changes caused by its reduction‐induced aggregation in vitro . A decrease in lifetime was observed for compound 1 in a buffered system activated by the biological reducing agent glutathione, thus suggesting a possible approach for designing responsive self‐aggregating lifetime imaging probes. Abstract : The value of a short life : The triggered aggregation of small molecules influences the properties of an attached fluorophore. The fluorescent cargo reports a reduced fluorescence lifetime in vitro and to an extent detectable in cells by fluorescence lifetime imaging microscopy, thus suggesting possible probe design for lifetime imaging of biological events and analytes.